A compendium of world sovereigns. - Venning, Timothy, author.
1 online resource (xvi, 562 pages)
Keywords: The Compendium of World Sovereigns series contains three volumes: Ancient, Medieval, and Early Modern. These volumes provide students with easy-to-access ⁰́₈who⁰́₉s who⁰́₉ with details on the identities and dates, ages and wives, where known, of heads of government in any given state at any time within the framework of reference. The relevant original and secondary sources are also listed in a comprehensive bibliography. The text provides a clear reference guide for students to who was who and when they ruled in the dynasties and other ruler-lists for the Ancient, Medieval, and Early Modern worlds ⁰́₃ primarily European and Middle Eastern but including available information on Africa and Asia and the pre-Columbian Americas. The trilogy accesses and interprets the original data plus any modern controversies and disputes over names and dating, reflecting on the shifts in and widening of focus in student and academic studies. Each volume contains league tables of rulers⁰́₉ ⁰́₈records⁰́₉, and an extensive bibliographical guide to the relevant personnel and dynasties, plus any controversies, so readers can consult these for extra details and know exactly where to go for which information. All relevant information is collected and provided as a one-stop-shop for students wishing to check the known information about a world Sovereign. The Medieval volume begins with the Byzantine Empire and moves through the Crusader States, the Islamic World, South and East Asia, Africa, the Mediterranean, and lastly Western and Eastern Europe. Compendium of World Sovereigns: Volume II Medieval provides students and scholars with the perfect reference guide to support their studies and to fact check dates, people, and places.